Composite finite-time control for PMSM with prescribed performance using disturbance compensation technique - Wang, Xinming; Wang, Xiangyu; Wang, Zuo; Xiao, Xi; Li, Shihua (Control engineering practice, 2023)
Permanent-magnet synchronous motors have attracted great attention and have been widely used in high performance industrial autonomous systems. In order to improve its control performance in the presence of external disturbances, the composite prescribed performance control (PPC) technique has been introduced. It can explicitly regulate the tracking performances like overshoot, convergence rate and steady-state-tracking error. But the current work only promises bounded or asymptotic behavior of the tracking error instead of finite-time convergence. To this end, a composite finite-time control scheme with prescribed performance is investigated for the speed regulation of permanent-magnet synchronous motor. The prescribed transient and steady performance constraints are considered beforehand by using the PPC technique. The external disturbances like load torque, adversely influencing the tracking performance, are estimated by finite-time disturbance observers. Then, based on the adding a power integrator technique, a composite finite-time speed regulation controller is designed by compensating the disturbance estimate via a feedforward manner. The finite-time stability of the closed-loop system is also analyzed rigorously. Finally, both comparative numerical simulations and experiments are conducted to verify the effectiveness of the proposed control scheme.